Antifouling activity of green-synthesized 7-hydroxy-4-methylcoumarin. (February 2016) - Pérez, Miriam; García, Mónica; Ruiz, Diego; Autino, Juan Carlos; Romanelli, Gustavo; Blustein, Guillermo
Abstract: In the search for new environmental-friendly antifoulants for replace metallic biocides, 7-hydroxy-4-methylcoumarin was synthesized according to green chemistry procedures. This compound was characterized by current organic analysis and its antifouling properties were firstly evaluated on the bivalve Mytilus edulis platensis in the laboratory. In the second stage, a soluble matrix antifouling coating formulated with this compound was assayed in marine environment. Laboratory experiments showed that 7-hydroxy-4-methylcoumarin was effective in inhibiting both the settlement as well as the byssogenesis of mussels. In addition, after exposure time in the sea, painted panels containing this compound showed strong antifouling effect on conspicuous species of the fouling community of Mar el Plata harbor. In conclusion, green-synthesized coumarin could be a suitable antifoulant candidate for marine protective coatings. Highlights: 7-hydroxy-4-methylcoumarin (1 ) was synthesized according to green chemistry procedures. Laboratory experiments showed that (1 ) had a strong anti-settlement activity. Antifouling performance of (1 ) was evaluated included in rosin-based coatings. Field trials showed that coating with (1 ) exhibited high antifouling performance. Green-synthesized coumarin is a suitable antifoulant candidate for marine coatings.